Sebaceous nevus: a retrospective study of 104 cases. - Mazeda, I.; Alvarenga, J.; Machado, S. (European Journal of Pediatric Dermatology, 2025)
Sebaceous nevus is a congenital hamartoma usually diagnosed at birth and typically benign. This 20-year retrospective study analyzed 104 pediatric cases to evaluate clinical evolution, histopathological findings, and therapeutic strategies. Most lesions were stable and localized to the scalp, with only one case of benign neoplastic transformation. Surgery was performed in selected cases due to progression or esthetic concerns, while over half of the patients were managed conservatively. These results underscore the low risk of malignancy of nevus sebaceous in childhood and suggest a cautious and individualized approach, reserving treatment for evolving or symptomatic lesions.